2021
DOI: 10.3390/nu13093037
|View full text |Cite
|
Sign up to set email alerts
|

Affordability of Different Isocaloric Healthy Diets in Germany—An Assessment of Food Prices for Seven Distinct Food Patterns

Abstract: Affordability of different isocaloric healthy diets in Germany—an assessment of food prices for seven distinct food patterns Background: For decades, low-fat diets were recommended as the ideal food pattern to prevent obesity, type 2 diabetes and their long-term complications. Nowadays, several alternatives considering sources and quantity of protein, fat and carbohydrates have arisen and clinical evidence supports all of them for at least some metabolic outcomes. Given this variety in diets and the lack of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
(47 reference statements)
2
12
0
Order By: Relevance
“…We think that the ketogenic diet could be a very useful tool to consider in the management of lipedema; certainly this was a particularly favorable case, as in other situations, there are different aspects, but also less compliance (this aspect could be moderated by alternating periods of a ketogenic diet with periods of a low-carb diet; i.e., with an intake of carbohydrates around 100-150 g per day-we in fact are working on a program of this type on a large scale). The cost of the program, as pointed out by Kabisch et al [38], was not a secondary factor, even in the specific case; perhaps also thanks to the good results, it was not a problem.…”
Section: Discussionmentioning
confidence: 85%
“…We think that the ketogenic diet could be a very useful tool to consider in the management of lipedema; certainly this was a particularly favorable case, as in other situations, there are different aspects, but also less compliance (this aspect could be moderated by alternating periods of a ketogenic diet with periods of a low-carb diet; i.e., with an intake of carbohydrates around 100-150 g per day-we in fact are working on a program of this type on a large scale). The cost of the program, as pointed out by Kabisch et al [38], was not a secondary factor, even in the specific case; perhaps also thanks to the good results, it was not a problem.…”
Section: Discussionmentioning
confidence: 85%
“…Similar to our findings, a recent study in Germany which investigated the food costs of four week sample menus using minimum retail prices estimated food costs per day of 5.17 EUR/day (2.59 EUR/1000 kcal) and 5.69 EUR/day (2.85 EUR/1000 kcal) for 10–13 year old girls and boys on a vegetarian diet, respectively. In this study, the food costs of a vegan diet were about 1 EUR/day higher (6.17 EUR/day for girls, 6.97 EUR/day for boys) [ 33 ]. This higher estimated total daily food costs may be due to a higher assumed energy requirement (PAL 1.6, i.e., 2000 kcal/day for girls, 2200 kcal for boys).…”
Section: Discussionmentioning
confidence: 99%
“…Energy requirements and thus the amount of food needed is the most important determinant of total food costs [ 5 ]. Therefore, daily food costs increase with age and are higher for boys than for girls [ 5 , 33 ]. That is why the present evaluation considered both daily food costs and food costs, standardised to energy intake.…”
Section: Discussionmentioning
confidence: 99%
“…( Rubini et al, 2021 ) A German study compared monetary costs of seven reasonably healthy dietary patterns and found that the low fat vegetarian diet was the most affordable, with the other dietary patterns ranging from 10% to 70% more costly. ( Kabisch et al, 2021 ) An analysis from the U.K. found that healthy-and-sustainable diets could be affordable among all income quintiles, but that some adjustments might be needed. ( Reynolds et al, 2019 ) Economic savings from transitioning towards a plant-based diet may go beyond the purchase costs of foods.…”
Section: Economic Costsmentioning
confidence: 99%